Incentives for Information Production and Disclosure: Comment - Seidmann, Daniel J. (Quarterly Journal of Economics, 1987)
Journal Article Incentives for Information Production and Disclosure: Comment Get access Daniel J. Seidmann Daniel J. Seidmann Trinity College, Dublin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 102, Issue 2, May 1987, Pages 445–452, https://doi.org/10.2307/1885073 Published: 01 May 1987